Porous zeolitic imidazolate frameworks assembled with highly-flattened tetrahedral copper(ii) centres and 2-nitroimidazolates. Issue 27 (16th March 2023) - Jung, Cheolwon; Choi, Sang Beom; Park, Jaewoo; Jung, Minji; Kim, Jonghoon; Oh, Hyunchul; Kim, Jaheon
Abstract : Cu-ZIF-gis has 2.4 Å cylindrical pores that can adsorb H2 gas, and Cu-ZIF-rho has 19.8 Å cages with a BET surface area of 1320 m 2 g −1 . Abstract : Cu(ii )-based zeolitic imidazolates (Cu-ZIFs), Cu-ZIF-gis and -rho, formulated as Cu(nIm)2 (nIm = 2-nitroimidazolate) have highly-flattened tetrahedral coordination geometry. Cu-ZIF-gis has 2.4 Å cylindrical pores that can adsorb H2 gas, and Cu-ZIF-rho has 19.8 Å cages with a BET surface area of 1320 m 2 g −1 .